1999
DOI: 10.1038/44409
|View full text |Cite
|
Sign up to set email alerts
|

Probing the human stereoscopic system with reverse correlation

Abstract: Our two eyes obtain slightly different views of the world. The resulting differences in the two retinal images, called binocular disparities, provide us with a stereoscopic sense of depth. The primary visual cortex (V1) contains neurons that are selective for the disparity of individual elements in an image, but this information must be further analysed to complete the stereoscopic process. Here we apply the psychophysical technique of reverse correlation to investigate disparity processing in human vision. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 18 publications
1
90
0
Order By: Relevance
“…Complex cells do show disparity tuning for AC-RDS, but with reduced amplitude (Cumming & Parker, 1997;Ohzawa et al, 1997). With a completely separate experimental approach, Neri et al (1999) found that disparity-specific psychophysical "filters" derived from human observers also show an attenuated response for anticorrelated stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…Complex cells do show disparity tuning for AC-RDS, but with reduced amplitude (Cumming & Parker, 1997;Ohzawa et al, 1997). With a completely separate experimental approach, Neri et al (1999) found that disparity-specific psychophysical "filters" derived from human observers also show an attenuated response for anticorrelated stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…Although the energy-neuron model can easily be extended in order to suppress responses to aRDSs (Lippert et al 2000;Lippert and Wagner 2001), it is instructive to evaluate the representation of aRDS disparity in populations of the standard model neuron. This allows a test of the necessity of the postulation of high-level disparity detectors that do not respond to aRDSs (Cumming and Parker 1997;Neri et al 1999;Nieder and Wagner 2001). The disparity represented by energy neurons should have phase with a sign opposite to the stimulus disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Anticorrelation has been shown to disrupt static disparity mechanisms (Cogan et al 1995;Cumming et al 1998;Neri et al 1999), while maintaining monocular velocity information (Harris and Rushton 2003) and thus retaining IOVDs in the presence of greatly degraded disparity-based signals. In addition, our group has previously used sparse, anticorrelated dot displays to isolate the contribution of the IOVD cue (Rokers et al 2008(Rokers et al , 2009.…”
Section: Motion Cue Conditions: Full Iovd and CDmentioning
confidence: 99%